Malignant Melanoma Presenting as Obstructive Jaundice Secondary to Metastasis to the Ampulla of Vater - Marks, Joshua A; Rao, Atul S; Loren, David; Witkiewicz, Agnes; Mastrangelo, Michael J; Berger, Adam C (JOP. Journal of the Pancreas, 2010)
Context Malignant melanoma commonly metastasizes to the small intestine where it can cause pain, bleeding, and obstruction. However, jaundice from metastatic melanoma is relatively uncommon. Case report A case of known malignant melanoma presenting as new onset obstructive jaundice as a result of a rarely reported metastasis to the ampulla of Vater. Conclusion Multidisciplinary management of patients with metastatic melanoma is essential. Image: Images from the ERCP demonstrate a large, irregular, friable, soft mass at the ampulla.